PERMIAN CLIMATES: EVALUATING MODEL PREDICTIONS USING GLOBAL PALEOBOTANICAL DATA - Rees P.McA.; Ziegler A.M.; Gibbs M.T.; Kutzbach J.E.; Behling P.J. (My University, 1999)
The most recent global icehouse-hothouse climate transition in Earth history occurred in the Permian. Warmer polar conditions relative to today existed from the middle Permian through the Mesozoic and into the Cenozoic. We focus here on one particularly well-correlated middle Permian stage that postdated the deglaciation, the Wordian (267-264 Ma), integrating floral and lithological data to determine Wordian climates globally. Paleobotanical data provide the best means of interpreting terrestrial paleoclimates, often revealing important information in the con- tinuum between "dry" and "wet" end-member lithological indicators such as evaporites and coals. New statistical analyses of Wordian floras worldwide have enabled a greater understand- ing of original vegetation patterns and prevailing climate conditions. The derived climate inter- pretations are compared with new Wordian atmospheric general circulation model simulations. The model matches the data well in the tropics and northern high latitudes, but predicts colder conditions in southern high latitudes. We discuss possible reasons for this discrepancy.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская